THE EFFECT OF ESSENTIAL AMINO ACIDS USE IN CORN-POLLARD BASE RATIONS ON BALI PIGS PERFORMANCE - A. A. P., Wibawa; Sumadi, I K. (Majalah Ilmiah Peternakan; Vol 22 No 3 (2019): Vol. 22 No.3 (2019)DO - 10.24843/MIP.2019.v22.i03.p02, 2019)
This study was conducted to determine the effect of supplementation of a mixture of essential amino acids (lysine, methionine and tryptophan) in traditional corn-polar based ration in bali pigs for 16 weeks. The design used in this study was a completely randomized design (CRD) with three treatments and each treatment had 4 replications, so in this study using 3 x 4 = 12 weaning bali pigs. The treatment were P0: basic ration mixed with corn and pollard; P1: Ration P0 + mixture of amino acids lysine, methionine and tryptophan; and P2: standard ration. Variables observed included initial body weight, final body weight, weight gain, ration consumption and ration conversion (FCR). Data were analyzed by analysis of variance, if there were significant differences P <0.05), the analysis continued with the analysis of Duncan. The results showed that supplementation of a mixture of lysine, methionine and tryptophan amino acids could increase the ration consumption13%, final body weight 18%, weight gain 27% and decrease FCR 11.61% compared with basic ration mixed with corn and pollard or traditional feed. It can be concluded that ration with mixture of amino acid increase feed consumption, body weigt, final body weight and feed efficiency.